Carleman estimates and some inverse problems for the coupled quantitative thermoacoustic equations by boundary data. Part II: some inverse problems - Cristofol, Michel; Li, Shumin; Shang, Yunxia (Mathematical methods in the applied sciences, 2023)
In this paper, we consider Carleman estimates and inverse problems for the coupled quantitative thermoacoustic equations. In the previous Part I of this paper, we established Carleman estimates for the coupled quantitative thermoa-acoustic equations by assuming that the coefficients satisfy suitable conditions. We apply Carleman estimates in the previous Part I to some inverse problems for the coupled quantitative thermoacoustic equations and prove stability estimates of the Hölder type.